Minor and rare earth elements as paleoenvironmental markers of late quaternary sediments in Marajo Island, Northern Brazil - Rossetti, Dilce; Munita, Casimiro Sepúlveda; Oliveira, Paulo Meira Silva (Geochimica Brasiliensis, 2013)
The recognition of estuarine deposits in the ancient record is problematic if based only on sedimentological studies due to the difficult assessment of both sedimentary processes and body geometry, particularly where only cores are available. Exploring proxies that can be used in combination with sedimentary parameters can improve the reconstruction of estuarine systems in the geological record. Geochemical tracers have good potential as paleoenvironmental proxies. However, additional studies are needed to further demonstrate their application for discriminating various estuarine environments. This approach was applied to a late Quaternary estuarine succession in northern Brazil. Multivariate analysis of trace and rare earth elements allowed distinguish five geochemical groups in agreement with previous interpretations of depositional environments consisting of fluvial, outer estuary, central estuarine basin, tidal flat, and lagoon. Statistical analyses allowed a clear distinction between fluvial-influenced and marine-influenced deposits. The distribution of geochemical tracers had strong effect of variations in salinity and pH that typify these depositional environments, though some of the changes also might be related to other processes, such as adsorption due to the influence of colloidal material, mineralogical influence, airborne deposition, and burrowing. The results lead to suggest that trace and rare earth elements are useful tools to distinguish depositional environments associated with ancient estuarine systems.